THE EFFECTIVENESS OF HAND HYGIENE PRACTICES IN REDUCING INFECTIONS IN HOSPITALS - Asadullo A. Bakirov; Gulsara A. Seifullaeva (Central Asian Journal of Medicine, 2025)
This article addresses the central role of hand hygiene in the prevention of hospital-acquired infections, presenting a comprehensive description of its principles, history, and modern applications. It emphasizes the importance of hand hygiene to physical health, traces its evolution in Central Asia as a whole and in Uzbekistan specifically, and recognizes international efforts to combat infectious diseases. The article also explores the current global hygiene practices and brushes on the thousand-year Muslim world’s tradition of hygiene as a prevention measure. Supported with a comparative table and precise citations, the article points out the efficacy of hand hygiene in healthcare settings and the ability to bridge past and current infection control efforts.